2006
DOI: 10.1029/2006pa001291
|View full text |Cite
|
Sign up to set email alerts
|

Southward shift of the Intertropical Convergence Zone in the western Pacific during the late Tertiary: Evidence from ferromanganese crusts on seamounts west of the Marshall Islands

Abstract: Hydrogenetic ferromanganese crusts were dredged from four seamounts in the western Pacific, OSM7, OSM2, Lomilik, and Lemkein, aligned in a NW‐SE direction parallel to Pacific Plate movement. The crusts consist of four well‐defined layers with distinct textural and geochemical properties. The topmost layer 1 is relatively enriched in Mn, Co, Ni, and Mo compared to the underlying layer 2, which is relatively enriched in Al, Ti, K, and Rb and Cu, Zn, and excess Ba. Textural and geochemical properties of layer 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…1C), allowing for the differences in its reconstructed position (Lyle et al, 2002;Kim et al, 2006). This is consistent with the distribution of Early Miocene biogeographic provinces that indicates that this was a period during which warm water masses extended to unusually high latitudes in the Northern Hemisphere.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…1C), allowing for the differences in its reconstructed position (Lyle et al, 2002;Kim et al, 2006). This is consistent with the distribution of Early Miocene biogeographic provinces that indicates that this was a period during which warm water masses extended to unusually high latitudes in the Northern Hemisphere.…”
Section: Discussionsupporting
confidence: 79%
“…Other estimates have been made for the ITCZ paleolatitude. Kim et al (2006) analyzed the changes in composition of ferromanganese crusts from seamounts in the western Pacifi c (Fig. 1C).…”
Section: Neogene Itcz Paleolatitudementioning
confidence: 99%
“…This model was largely based on the position of the smectite-illite transition that marks the boundary between wind-blown clay derived from Asia and that from Central and South America in the central Pacific Ocean (Lyle et al 2002). In the western Pacific, a less dramatic migration southward was noted on the basis of the composition of manganese crusts that are dependent on biologic and detrital fluxes (Kim et al 2006). As the monsoon weakened, this band of intense rainfall would have migrated south and became positioned over the region where the Inner Lesser Himalaya are now exposed.…”
Section: Climate-tectonic Linkagesmentioning
confidence: 99%
“…These Pacific seamounts crusts generally consist of a lower (older) phosphatized layer and an upper (younger) non-phosphatized layer (e.g., McMurtry et al, 1994;Koschinsky et al, 1997;Hein et al, 1993Hein et al, , 1999. Recent detailed descriptions (Pan et al, 2005;Kim et al, 2005Kim et al, , 2006, however, have shown that each of these layers is itself divided into two distinct layers for a total of four layers. The younger two layers of Fe-Mn crust, which formed after phosphatization by carbonate fluorapatite, are respectively characterized by mottled and porous or vuggy (inner; Layer 2), and massive (outer; Layer 1) texture (Pan et al, 2005;Kim et al, 2005Kim et al, , 2006.…”
Section: Compositional Change Through the Growth Of Nodulesmentioning
confidence: 99%